2014
DOI: 10.1002/2014jb011096
|View full text |Cite
|
Sign up to set email alerts
|

Pyroclast Tracking Velocimetry illuminates bomb ejection and explosion dynamics at Stromboli (Italy) and Yasur (Vanuatu) volcanoes

Abstract: A new image processing technique-Pyroclast Tracking Velocimetry-was used to analyze a set of 30 high-speed videos of Strombolian explosions from different vents at Stromboli (Italy) and Yasur (Vanuatu) volcanoes. The studied explosions invariably appear to result from the concatenation of up to a hundred individual pyroclast ejection pulses. All these pulses share a common evolution over time, including (1) a non-linear decrease of the pyroclast ejection velocity, (2) an increasing spread of ejection angle, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 46 publications
8
57
1
Order By: Relevance
“…This complexity might be manifest in the seismo-acoustic signatures of the explosions (e.g., Johnson and Lees, 2000;Lyons et al, 2012), and in the visual character of the explosions. We note, for instance, that recent high-speed videography studies have identified that gas escape during strombolian explosions is typically pulsatory Gaudin et al, 2014), suggesting greater complexity than simple bursting of an overpressured slug. Understanding the role that a viscous plug plays in modulating the dynamics of slug ascent and burst is, therefore, of considerable importance in the interpretation of the waveform and amplitude of generated pressure changes (Lane et al, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…This complexity might be manifest in the seismo-acoustic signatures of the explosions (e.g., Johnson and Lees, 2000;Lyons et al, 2012), and in the visual character of the explosions. We note, for instance, that recent high-speed videography studies have identified that gas escape during strombolian explosions is typically pulsatory Gaudin et al, 2014), suggesting greater complexity than simple bursting of an overpressured slug. Understanding the role that a viscous plug plays in modulating the dynamics of slug ascent and burst is, therefore, of considerable importance in the interpretation of the waveform and amplitude of generated pressure changes (Lane et al, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…An individual Bexplosion^is characterized by multiple, second-long Bpulses^and sub-second-long Bsubpulses^, each pulse being characterized by the ejection of particles at similar velocities which then decrease in time (Taddeucci et al 2012a;Gaudin et al 2014;Bombrun et al 2015). In addition we can observe multiple emission points during a single event.…”
Section: Terminologymentioning
confidence: 99%
“…James et al 2004James et al , 2006James et al , 2008Lane et al 2013), and field observations (e.g. Chouet et al 1974;Blackburn et al 1976;Ripepe et al 1993Ripepe et al , 2005Patrick et al 2007;Harris et al 2012;Taddeucci et al 2012a, b;Gaudin et al 2014;Bombrun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus the vent flow was active about 25-33% of the time. Recently, Gaudin et al (2014) have used particle tracking velocimetry-i.e. analysis of high speed (500 frame per second, 14 s long) video acquired in 2011 to measure pyroclast velocities from the Yasur vents-their velocity histograms show a modal velocity of 20 m/s, a median of~40 m/s and a maximum of perhaps 150 m/s.…”
Section: Spectral Analysis and Vent Velocitymentioning
confidence: 99%